Effect of wireless gateway on incoming self-similar traffic - ZHANG Jie; WU Yuan-ming (Tongxin xuebao)
In the analysis of the changes as the self-similar cable network data enters the wireless network through wire- less gateway, the simulation results show that, the self-similarity does not change when the gateway works on real-time forward or power control mode, and its buffer equals wireless channel capacity; the self-similarity and state duration of EAFRP model will increase when the gateway works on power control mode and its buffer is much greater than wireless channel capacity.